2003
DOI: 10.1042/bss0700179
|View full text |Cite
|
Sign up to set email alerts
|

Cystatins

Abstract: Chicken egg white cystatin was first described in the late 1960s. Since then, our knowledge about a superfamily of similar proteins present in mammals, birds, fish, insects, plants and some protozoa has expanded, and their properties as potent peptidase inhibitors have been firmly established. Today, 12 functional chicken cystatin relatives are known in humans, but a few evolutionarily related gene products still remain to be characterized. The type 1 cystatins (A and B) are mainly intracellular, the type 2 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
279
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 346 publications
(285 citation statements)
references
References 0 publications
3
279
0
3
Order By: Relevance
“…Interestingly, silencing of stratifin in oral squamous cell carcinomas occurred at very similar frequency as that of p16 INK4a and was significantly less frequent in HPV positive oral tumors (Gasco et al, 2002), which are also characterized by p16 INK4a positivity (Andl et al, 1998). The cysteine proteinase inhibitors Cystatin A and B are likely relevant for intracellular protein degradation as well as degradation of the extracellular matrix by cathepsins (for review, see Abrahamson et al (2003)). Cystatin B has also been found downregulated in esophageal squamous cell carcinoma, consistent with our results (Shiraishi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, silencing of stratifin in oral squamous cell carcinomas occurred at very similar frequency as that of p16 INK4a and was significantly less frequent in HPV positive oral tumors (Gasco et al, 2002), which are also characterized by p16 INK4a positivity (Andl et al, 1998). The cysteine proteinase inhibitors Cystatin A and B are likely relevant for intracellular protein degradation as well as degradation of the extracellular matrix by cathepsins (for review, see Abrahamson et al (2003)). Cystatin B has also been found downregulated in esophageal squamous cell carcinoma, consistent with our results (Shiraishi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it appears that efficient and sustained inhibition of the enzyme will be required to fully quench neutrophil granule protease activity [63]. Cathepsin C may itself be regulated by cystatin F. Cystatins are a family of proteinaceous cysteine protease inhibitors, some of which bind very tightly to cathepsin active sites [64]. We recently showed that cystatin F, which is principally found in immune cells, could inhibit cathepsin C [65].…”
Section: Activation Of Granule Serine Proteasesmentioning
confidence: 99%
“…Cysteine proteases can be involved in enhanced cell survival and proliferation, escape from immune surveillance, cell adhesion and migration, remodelling and invasion of the extracellular matrix (Nomura and Katunuma, 2005). Cystatins are potent inhibitors of endogenous mammalian lysosomal cysteine proteases and protect cells against uncontrolled proteolysis (Abrahamson et al, 2003). Disturbance of the balance between proteases and their cystatins can lead to irreversible damage and tumour development (Calkins and Sloane, 1995;Henskens et al, 1996).…”
Section: Introductionmentioning
confidence: 99%